High expression of nucleotide-binding oligomerization domain protein 1 correlates with poor prognosis and immune cell infiltration in Glioblastoma Multiforme patients - Hongyang Zhao; Beiwu Lan; Zenghui Zhao; Peining Zhu; Chong Wang; Yufei Gao (Discover Oncology)
Abstract Nucleotide-binding oligomerization domain protein 1 (NOD1) is one of the innate immune receptors that has been associated with tumorigenesis and abnormally expressed in various cancers. However, the role of NOD1 in Glioblastoma Multiforme (GBM) has not been investigated. We used the Tumor Immune Estimate Resource (TIMER) database to compare the differential expression of NOD1 in various tumors. NOD1 expression in GBM was further validated in the GEO database, and the survival of NOD1 was assessed by the Kaplan–Meier method. Clinical samples were collected to validate NOD1 expression. GSEA was carried out to expound on NOD1-related pathways involved in GBM. NOD1 co-expression and enrichment analysis were performed using the Linked Omics database and R software. The relationship between immune infiltrates and NOD1 expression was assessed by TIMER. Besides, the correlation between NOD1 and immune signatures (immunomodulators and chemokine) was evaluated by TISIDB. We found that NOD1 expression was significantly upregulated in GBM patients, and higher expression of NOD1 was associated with a poor prognosis. GSEA and enrichment analysis revealed that NOD1 might play a vital role in immune response and GBM progression. TIMER analysis showed a positive correlation between NOD1 expression and 17 types of tumor-infiltrating immune cells. Moreover, NOD1 expression was positively correlated with the expression of chemokine and immunomodulators in GBM. Overall, our findings suggest that NOD1 is a promising prognostic biomarker and is associated with immune cell infiltration in GBM, making it a potential diagnostic biomarker for this aggressive brain cancer.